1986
DOI: 10.1016/s0006-3495(86)83727-4
|View full text |Cite
|
Sign up to set email alerts
|

A milling crowd model for local and long-range obstructed lateral diffusion. Mobility of excimeric probes in the membrane of intact erythrocytes

Abstract: A new model for lateral diffusion, the milling crowd model (MC), is proposed and is used to derive the dependence of the monomeric and excimeric fluorescence yields of excimeric membrane probes on their concentration. According to the MC model, probes migrate by performing spatial exchanges with a randomly chosen nearest neighbor (lipid or probe). Only nearest neighbor probes, one of which is in the excited state, may form an excimer. The exchange frequency, and hence the local lateral diffusion coefficient, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 33 publications
(32 reference statements)
4
49
1
Order By: Relevance
“…By contrast, lipid lateral diffusion measured in liposomes made from the mitochondrial lipids showed that (i) the difference between the two membranes was much smaller (50% only); (ii) there was no difference between liposomes and mitochondrial membranes in fad2 system, indicating that the high lipid mobility found in mutant mitochondrial membranes was mainly due to its low protein density. This hypothesis is in good agreement with reports showing that lateral diffusion of lipids in complex membranes is significantly reduced when proteins are incorporated in the bilayer (31,32). On the other hand, it is interesting to note that the activation energy of lipid lateral diffusion was lower in wild type mitochondrial membranes than in fad2 membranes or in liposomes.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, lipid lateral diffusion measured in liposomes made from the mitochondrial lipids showed that (i) the difference between the two membranes was much smaller (50% only); (ii) there was no difference between liposomes and mitochondrial membranes in fad2 system, indicating that the high lipid mobility found in mutant mitochondrial membranes was mainly due to its low protein density. This hypothesis is in good agreement with reports showing that lateral diffusion of lipids in complex membranes is significantly reduced when proteins are incorporated in the bilayer (31,32). On the other hand, it is interesting to note that the activation energy of lipid lateral diffusion was lower in wild type mitochondrial membranes than in fad2 membranes or in liposomes.…”
Section: Discussionsupporting
confidence: 93%
“…6) may indicate the temperature-induced dissociation of ground-state complex, the common event in static quenching [22,25] or in a more subtle way, the decrease of viscosity-mediated diffusional constraints. Additionally, the obstacled diffusion per se [34] due to protein circumference in small rHDL may appreciably contribute into lower D L values obtained for CPD diffusion in the present study in comparison to other studies of lateral diffusion in larger membrane structures [20,23,34].…”
Section: Discussioncontrasting
confidence: 79%
“…The coefficients of lateral diffusion calculated with Eqs. (1) and (2) for diffusion of the whole probe population (Table 1) varied as 2 10 À8 cm 2 s À1 for rHDL with POPC to 0.3 10 À8 cm 2 s À1 for rHDL with DPPC, being lower D L values (10 À8 -10 À7 cm 2 s À1 ) obtained for lateral diffusion in large membrane structures with pyrene excimerization and other approaches [20,23,34]. However, the difference markedly diminished after adjustment of D L values for probe fraction capable to fast exchange in CETP reaction (Table 1).…”
Section: Quenching Sphere-of-action Modelmentioning
confidence: 91%
“…Eisinger et al (24) recently published a model for lipid diffusion in complex membranes. In this model, impermeable domains such as proteins are spatially fixed, unlike the model developed in this paper.…”
Section: Discussionmentioning
confidence: 99%